2020
DOI: 10.1016/j.jinf.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of severe acute respiratory syndrome coronavirus 2 reactivation

Abstract: s u m m a r yObjectives: Previous studies on the pneumonia outbreak caused by the 2019 novel coronavirus disease (COVID-19) were based on information from the general population. However, limited data was available for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reactivation. This study aimed to evaluate the clinical characteristics of the SARS-CoV-2 reactivation. Methods: Clinical records, laboratory results, and chest CT scans were retrospectively reviewed for 55 patients with laboratory-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
346
2
19

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(381 citation statements)
references
References 7 publications
7
346
2
19
Order By: Relevance
“…To date, it is not proven that a patient that recovered from a previous infection to COVID-19 developed a complete and lasting immunity to the disease. In fact, reactivation of the disease [34] or even reinfection have been reported [35]. Our suggested preventive measures should be followed until herd immunity is achieved and the following patient categories are properly identified: * People aged 70 or older, people under 70 with an underlying health condition (chronic respiratory diseases, chronic heart disease, chronic kidney disease, chronic liver disease, chronic neurological conditions, diabetes, problems with spleen, a weakened immune system due to conditions such as HIV and AIDS or medicines, a body mass index (BMI) of 40 or above), pregnant women [36].…”
Section: Covid-19 Prevention In Dentistrymentioning
confidence: 99%
“…To date, it is not proven that a patient that recovered from a previous infection to COVID-19 developed a complete and lasting immunity to the disease. In fact, reactivation of the disease [34] or even reinfection have been reported [35]. Our suggested preventive measures should be followed until herd immunity is achieved and the following patient categories are properly identified: * People aged 70 or older, people under 70 with an underlying health condition (chronic respiratory diseases, chronic heart disease, chronic kidney disease, chronic liver disease, chronic neurological conditions, diabetes, problems with spleen, a weakened immune system due to conditions such as HIV and AIDS or medicines, a body mass index (BMI) of 40 or above), pregnant women [36].…”
Section: Covid-19 Prevention In Dentistrymentioning
confidence: 99%
“…A recently identified clinical phenomenon is reactivation of COVID‐19 infection in a subset of patients following recovery from initial disease. Although it has not yet been widely reported in the peer‐review medical literature, a report by Ye et al 8 identified reactivation in five patients from a cohort of 55 patients from China. Notably, influenza and H7 avian influenza virus were excluded by additional testing, but repeat testing for COVID‐19 does not appear to have been performed.…”
Section: Introduction: Epidemiology and Clinical Features Of The 2019mentioning
confidence: 99%
“…Unfortunately, though, SARS-CoV-2 reactivation and clinical deterioration have been reported in patients after hospital discharge 9 . Besides, some recovered patients can still excrete SARS-CoV-2, as demonstrated by the presence of viral nucleic acids in throat specimens 10 .…”
Section: Introductionmentioning
confidence: 99%